P-516 Cell-type specific role of Fragile X Mental Retardation polyglycine protein in blood of women with Fragile X Mental Retardation 1 gene premutation. (30th June 2022) - Nguyen, X.P; Adriana, V; Birgitta, M; Jens E, D; Katrin, H; Thomas, S; Julia, R
Abstract: Study question: What cell type is specific for the expression of FMRpolyG of FMR1 premutation (PM) in peripheral mononuclear blood cells (PMBC) and how can this impact female fertility? Summary answer: The expression of FMRpolyG is significantly higher in T cells from peripheral blood mononuclear cells (PBMCs) of FMR1 PM carriers. What is known already: Fragile X-associated primary ovarian insufficiency (FXPOI) is characterized by oligo/amenorrhea and hypergondotropic hypogonadism and is caused by expansion of the CGG-repeat in the 5'UTR of FMR1 . Autoimmunity is highly associated with POI and in FMR1 -PM activated inflammatory state and immune response have been discovered. RAN-translation dependent on variable CGG-repeat length is thought to cause FXPOI due to production of the polyglycine-containing-FMR1-protein, FMRpolyG. Colocalization of ubiquitin and FMRpolyG was recently demonstrated in ovarian stromal and mural granulosa cells from FMR1 PM carriers. Our previous data have also shown that FMRpolyG is aggregated in ubiquitin-positive inclusions in PBMCs from PM carriers. Study design, size, duration: PBMCs and granulosa cells (GCs) from women with PM (5) and women without PM (10) (controls) were examined by immunofluorescence staining (IF) for the presence of inclusions positive for ubiquitin and FMRpolyG. Cell lysis and protein extraction samples were subjected to Western blot analysis (WB) to detect FMRP and FMRpolyG. Flow cytometric analyzes (FACs) were performed to determine cell type-specific expression of FMRpolyG. Participants/materials, setting, methods: PBMCs were isolated from peripheral blood using Ficoll-Paque. PBMCs were fixed, IF stained for FMRpolyG and ubiquitin, and analyzed by fluorescence microscopy. WB was used to detect the expression of FMRP, FMRpolyG in extracted protein from lymphocytes and GCs. PBMCs were surface stained with CD3, CD14 and CD19 antibodies and later intracellular stained with FMRpolyG and ubiquitin for FACs analysis. Main results and the role of chance: FMRpolyG aggregates were detected as ubiquitin-positive inclusions in PBMCs from PM carriers, whereas only weak signal without inclusions was detected in controls. We detected FMRpolyG as a 15- to 25-kDa protein in PBMCs from two FMR1 PM carriers with 124 and 81 CGG repeats, a PM range that is supposed to carry the highest risk to develop FXPOI within all PM carriers. Using FACs, we found that the expression levels of FMRpolyG were significantly higher in the FMR1 PM carriers than in the group without PM (3.5-fold, p = 0.03). Both FMR1 PM and non-PM groups showed normal distribution of T cells (58.38% ± 11.54 and 58.72% ± 6.16, respectively). However, FMRpolyG fluorescence intensity was 28.98-fold higher (p = 0.01) in the T cells of FMR1 PM carriers than in those of women without PM. FMRpolyG expression levels of B cells (CD19+) and monocytes (CD14+) were comparable in both groups. Of note, the ubiquitin-positive cells of FMR1 PM carriers had significantly higher expression levels of FMRpolyG than those of non-PM carriers (17.84-fold, p < 0.0001). Limitations, reasons for caution: More patients are needed to support the present results. Further studies on the possible consequences of these FMRpolyG-positive inclusions in PM carriers are also advisable. Wider implications of the findings: We found for the first time FMRpolyG aggregates in the peripheral blood of PM-carriers and a significant increase in FMRpolyG expression in T cells from PM-carriers. These results suggest that FMRpolyG may have a toxic potential and play an immunological role in ovarian damage, finally triggering the development of FXPOI. Trial registration number: RE 3647/1-1 and /1-2